Effect of cold drawn deformation on mechanical properties of low carbon steel due to changes in grain size (2011)
The effect of grain size on the mechanical properties of cold-drawn low carbon steel was investigated. Low carbonsteel specimen cold-drawn to 20%, 25%, 40% and 55% as applicable for the manufacture of 4 inches, 3 inches,21/2 inches and 2inches nail were obtained. The study was aimed at providing experimental result for the understanding of grain size effects which occur with increasing degree of cold-drawn deformation in low-carbon steel used for nail manufacture.The micrographs of steel were obtained using optical microscopy(OM) observation for 20%, 25%,40% and 55% degrees of drawn deformation. From the OM micrographs the counting method as stated in the ASTME E112 standard for grain size was used to determine the grain size of the steel on the micrograph at the different degrees of deformation. The tensile strength, yield strength, brinnel hardness, and toughness of the materials were obtained from mechanical tests. It was shown that the tensile strength, yield strength, toughness and hardness follow quite closely the hall-petch equation.